2016
DOI: 10.1002/adhm.201600574
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Specific In Vivo Bioorthogonal Ligation via Chemical Modulation

Abstract: A critical limitation of bioorthogonal click chemistry for in vivo applications has been its low reaction efficiency due to the pharmacokinetic barriers, such as blood distribution, circulation, and elimination in living organisms. To identify key factors that dominate the efficiency of click chemistry, here we propose a rational design of near-infrared fluorophores containing tetrazine as a click moiety. Using trans-cyclooctene-modified cells in live mice, we found that the in vivo click chemistry could be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 27 publications
3
10
0
Order By: Relevance
“…WuA108 and WuA110 include +1/−3 and +1/−5, respectively, and the final surface charges of −2 and −4, respectively. The log D value (related to hydrophilicity/lipophilicity) of each fluorophore is between −3.2 and 3.0, determined using Marvin and JChem calculator plugins (ChemAxon, Budapest, Hungary) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WuA108 and WuA110 include +1/−3 and +1/−5, respectively, and the final surface charges of −2 and −4, respectively. The log D value (related to hydrophilicity/lipophilicity) of each fluorophore is between −3.2 and 3.0, determined using Marvin and JChem calculator plugins (ChemAxon, Budapest, Hungary) …”
Section: Resultsmentioning
confidence: 99%
“…The bioconjugation of NIR fluorophores on the surface of exosomes was made by converting the carboxylic group into the amine‐reactive N ‐hydroxysuccinimide (NHS) ester . After vigorous stirring for 1 h, the NIR fluorophore‐conjugated exosomes (NIR‐exo) were purified using a P‐6 size exclusion column to remove unbound free fluorophores.…”
Section: Resultsmentioning
confidence: 99%
“…Koo et al have also shown the effects of pharmacokinetics of injected molecules on click chemistry in vivo. 99 They conjugated Tz groups with uorescent dyes of various chemical structures. In mice, the change of charge or hydrophobicity changed their biodistribution, circulation, and secretion.…”
Section: Discussionmentioning
confidence: 99%
“…As an in vivo application, we labeled the HA-pep3 with Cy5.5 dye and injected it into the tail vein of mice. Biodistribution of the injected materials is determined by various factors including size, charge, and hydrophobicity 36 . For successful in vivo imaging, the materials need to provide sufficient contact time with the target, fast and strong binding to the target, and minimization of non-specific binding to other tissues.…”
Section: Discussionmentioning
confidence: 99%